Correlation of design parameters with performance for electrostatic precipitator. Part I. 3D model development and validation - He, Zhongjie (2020)
As the first part of a two-paper series, this paper develops a three-dimensional model that describes corona discharge, turbulent flow, particle charging and tracking in electrostatic precipitators (ESP). To capture the shielding effects between discharge wires in a multi-wire ESP, the corona-discharge-induced space charge density at an arbitrary point between the discharge wire and grounded plates is specified as the sum of two components: (i) a uniform value on the wire surface which is resolved individually for each wire; and (ii) a space-dependent variation relative to the uniform part. The present model is solved with the finite element method and validated with experimental and numerical results from literature. Good agreement is obtained and illustrated in terms of distributions of electric potential, current density, electrohydrodynamic flow pattern, and particle trajectories, as well as corona current and particle collection efficiency. This validated model will be applied in Part II and integrated with the design-of-experiment approach to analyze both individual and interactive effects of design parameters on ESP performance.